PERANCANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE ANIMATE PADA PEMBELAJARAN TIK UNTUK KELAS XI DI SMAN 4 PARIAMAN - Anggi Fradila; Liza Efriyanti; Supratman Zakir; Hari Antoni Musril (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted from the problems that the authors found during observations at SMAN 4 Pariaman which so far the teacher has not maximized the use of technology in ICT learning, students only rely on verbal learning from the teacher, so students get bored quickly when learning takes place and have difficulty understanding the material taught by the teacher. . Therefore, the author designed Adobe Animate-based learning media so that it can be an alternative learning media. The purpose of this research is to produce a design for supporting ICT learning media based on Adobe Animate that is valid, practical and effective. The method used in this study is the Research and Development (R&D) method using the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept (conception), design (design), collecting material (material collection). ), assembly (manufacture), testing (testing), and distribution (distribution). And the product test carried out in this research is the validity test given to lecturers who are field experts or field experts, practicality tests are carried out by ICT subject teachers and effectiveness tests are given to students at SMAN 4 Pariaman class XI. Based on the results of product testing that has been carried out by the author of the validity test, the average value is 0.78 which is declared valid, for the practicality test, the average value is 0.75 which is declared high practicality and for the effectiveness test, the average value is obtained. the average is 0.91 which is declared high effectiveness. Keywords: Learning media, ICT, Adobe Animate.